Investigation of a bidirectional thulium-doped fiber amplifier based fiber laser with a Japanese-geta shape. (September 2022) - Guan, Biao; Yan, Fengping; Qin, Qi; Liu, Yan; Cheng, Dan; Li, Ting; Yu, Chenhao; Yang, Dandan; Kumamoto, Kazuo; Zhou, Hong; Suo, Yuping; Feng, Ting
Highlights: A thulium-doped fiber amplifier–based Japanese geta–shaped fiber laser was proposed and demonstrated. The stability of the proposed fiber laser was tested for 60 min with fluctuations of the center wavelength and output power of less than 0.003 nm and 0.104 dB, respectively. A maximum OSNR of ∼30.598 dB and a minimum threshold power of ∼1.118 W were obtained under bidirectional amplification. Abstract: A thulium-doped fiber amplifier–based Japanese geta–shaped fiber laser was proposed and demonstrated, and a homemade uniform fiber Bragg grating was used to select the desired lasing channel. The experiment was carried out under three different configurations, and the maximum transmission power of the amplified spontaneous emission was obtained in the configuration of bidirectional amplification. The stability of the proposed fiber laser was tested for 60 min with fluctuations of the center wavelength and output power of less than 0.003 nm and 0.104 dB, respectively. A maximum optical signal-to-noise ratio of ∼30.598 dB and a minimum threshold power of ∼1.118 W were obtained under bidirectional amplification. The maximum slope efficiency of 6.57% was obtained under backward amplification. In addition, the tunability of the proposed fiber laser was investigated under different configurations. The proposed fiber laser was found to be well suited in the areas of optical fiber communication and sensor systems.